Keeping the shape of the organization by adequate HR initiatives: Agrani Bank Limited - Rajo, Md. Abu Naser (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.